2018
DOI: 10.1016/j.jdermsci.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative effects of 17 β-estradiol and genistein in human skin fibroblasts and keratinocytes

Abstract: 17 β-estradiol/genistein protected fibroblasts/keratinocytes against peroxidation by modulating oxidant/antioxidant system and mitochondria membrane potential, through mechanisms related to ERs and GPER30 and kinases activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 64 publications
3
42
0
Order By: Relevance
“…This effect remains active after the removal of the original driving force by the switch from hyperglycemia to normoglycemia. This partly explains the potential mechanism of the hyperglycemia memory (8, 9), and our findings show that ERβ expression or activation (28) may be able to break this kind of loop, and subsequently diminish the hyperglycemia memory.…”
Section: Discussionsupporting
confidence: 55%
“…This effect remains active after the removal of the original driving force by the switch from hyperglycemia to normoglycemia. This partly explains the potential mechanism of the hyperglycemia memory (8, 9), and our findings show that ERβ expression or activation (28) may be able to break this kind of loop, and subsequently diminish the hyperglycemia memory.…”
Section: Discussionsupporting
confidence: 55%
“…Fibroblasts are the main sites for collagen and elastic fibres synthesis. Although skin fibroblasts are located in the dermis under the epidermis, they are more subjected to oxidative damage . In our experiment, high‐glucose stimulation attenuated proliferation and migration while enhanced oxidative stress in mice skin fibroblasts, which was most serious in that from SIRT3 knockout mice.…”
Section: Discussionmentioning
confidence: 58%
“…Research showed that genistein is a phytoestrogen that can prevent the aging process due to its antioxidant activity. Genistein can decrease the activation/expression of eNOS and iNOS induced by hydrogen peroxide-induced peroxidative stimulation [19]. In addition to its antioxidant properties and estrogenic/antiestrogenic activity, genistein has several molecular roles, including inhibition of protein tyrosine kinase and topoisomerase II and degradation of phosphatidylinositol and proteins involved in multidrug resistance in cancer cells.…”
Section: Genistein As Antioxidantmentioning
confidence: 99%